Ground state structures of Fe(2)O(4-6)(+) clusters probed by reactions with N(2) - Xue, Wei; Yin, Shi; Ding, Xun-Lei; He, Sheng-Gui; Ge, Mao-Fa (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2009)
Reactions of small cationic iron oxide clusters (Fe(2)O(4-6)(+)) with N(2) are investigated by experiments and first principle calculations. The cationic iron oxide clusters are generated by reaction of laser ablated iron plasma with O(2) in a supersonic expansion, and are reacted with N(2) in a fast flow reactor at near room temperature conditions. Cluster cations are detected by a time-of-flight mass spectrometer. The substitution reaction Fe(2)O(n)(+) + N(2) --> Fe(2)O(n-2)N(2)(+) + O(2) is observed for n = 5 but not for n = 4 and 6. Density functional theory calculations predict that the low-lying energy structures of Fe(2)O(4-6)(+) are with side-on (eta(1)-O(2)) or end-on (eta(2)-O(2)) bonded molecular oxygen unit(s). The calculations further predict that the substitution of eta(1)-O(2) and eta(2)-O(2) in Fe(2)O(4,6)(+) clusters by N(2) is exothermic and subject to negative and positive overall reaction barriers, respectively, at room temperature. We thus propose that the ground state structures of Fe(2)O(4)(+) and Fe(2)O(6)(+) contain eta(2)-O(2). In contrast, both the experiment and theory favor a eta(1)-O(2) in the ground state structure of Fe(2)O(5)(+).